Electroacupuncture alleviates chemotherapy‐induced pain through inhibiting phosphorylation of spinal CaMKII in rats. (16th October 2017) - Zhang, Y.; Li, A.; Xin, J.; Ren, K.; Berman, B.M.; Lao, L.; Zhang, R.‐X.
Abstract: Background: Current medical treatments for chemotherapy‐induced pain (CIP) are either ineffective or have adverse side effects. Acupuncture may alleviate CIP, but its effectiveness against this condition has not been studied. Paclitaxel causes neuropathic pain in cancer patients. Methods: We evaluated the effects of electroacupuncture (EA) on paclitaxel‐induced CIP in a rat model. Paclitaxel (2 mg/kg) or vehicle was injected (i.p.) on alternate days of 0–6. The resulting pain was treated with 10 Hz/2 mA/0.4 ms pulse EA for 30 min at the equivalent of human acupoint GB30 (Huantiao) once every other day between days 14 and 26. For sham control, EA needles were inserted into GB30 without stimulation. Von Frey filaments with bending forces of 2–8 g and 15 g were used to assess mechanical allodynia and hyperalgesia, respectively, on day 13 and once every other day between 14–26 days and then for 2–3 weeks after EA treatment. Results: Compared to sham control, EA significantly alleviated paclitaxel‐induced mechanical allodynia and hyperalgesia, as shown by less frequent withdrawal responses to the filaments. The alleviation of allodynia/hyperalgesia lasted up to 3 weeks after the EA treatment. EA significantly inhibited phosphorylation of Ca 2+ /calmodulin‐dependent protein kinase II (CaMKII) in the spinal cord. KN‐93, a selective inhibitor of p‐CaMKII, inhibited mechanical allodynia/hyperalgesia and p‐CaMKII. 5‐HT1A receptor antagonist blocked EA inhibition of allodynia/hyperalgesia and p‐CaMKII. Conclusions: Electroacupuncture activates 5‐HT 1A receptors in the spinal cord and inhibits p‐CaMKII to alleviate both allodynia and hyperalgesia. The data support acupuncture/EA as a complementary therapy for CIP. Significance: Electroacupuncture (EA) activates spinal 5‐HT1A receptors to inhibit p‐CaMKII to alleviate paclitaxel‐induced pain. Acupuncture/EA may be used as a complementary therapy for CIP.